Female infant with apert syndrome and high imperforate anus without fistula - Setya Mithra Hariastuti (Elsevier, 2021)
Apert syndrome (AS) is a rare type of congenital craniofacial dysmorphic and severe syndactyly of the hands and feet. Fibroblast growth factor receptor (FGFR) gene mutations are suspect to be involved in this anomaly. The distinct features are craniosynostosis-a condition of premature closure of skull's sutures-, midface hypoplasia-an incomplete development of the middle of the face-, and syndactyly-webbed fingers or toes-. The anorectal malformations (ARMs) associations with AS is rare, and the genetic link is highly complex. Only 12.7% of ARMs cases were associated with a syndrome that has a well-known impact on intellectual development, including AS. To our knowledge, this is the first reported case of AS with a high imperforate anus without fistula.